2020
DOI: 10.1016/j.atherosclerosis.2020.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Intestine-specific DGAT1 deficiency improves atherosclerosis in apolipoprotein E knockout mice by reducing systemic cholesterol burden

Abstract: Background and aims Acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1) is the rate-limiting enzyme catalyzing the final step of triglyceride synthesis by esterifying a diglyceride with a fatty acid. We have previously shown that apolipoprotein E-knockout ( ApoE −/− ) mice lacking Dgat1 have reduced intestinal cholesterol absorption and potentiated macrophage cholesterol efflux, and consequently, exhibit attenuated atherogenesis. However, he-matopoietic Dgat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Immunohistochemical analysis was performed on small intestine tissues to observe the expression of NPC1L1 and HNF-1α as previously described. , In brief, the small intestine was fixed with 4% paraformaldehyde and then embedded in paraffin. Paraffin wax blocks were prepared and sliced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analysis was performed on small intestine tissues to observe the expression of NPC1L1 and HNF-1α as previously described. , In brief, the small intestine was fixed with 4% paraformaldehyde and then embedded in paraffin. Paraffin wax blocks were prepared and sliced.…”
Section: Methodsmentioning
confidence: 99%
“…The aortic atherosclerosis lesions were determined according to the method described previously . Briefly, the active vessel cavity was rinsed with normal saline until the rinse solution became clear.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, cell lines may provide an alternative for modeling when mouse models are not relevant to the human biology. Such is the case for DGAT1, where the homologous DGAT1 gene and its cousin DGAT2 are not expressed in rodents as in humans, and deletion of one or other of DGAT genes in mice does not phenocopy the syndrome in humans ( Chen and Farese, 2005 ; Gluchowski et al, 2017 ; Vujić et al, 2020 ). Nevertheless, DGAT1 knockdown could be performed in CaCo2-BBe cells with recapitulation of the impairment in brush border integrity and amelioration of the phenotype with culturing without lipids in the apical media ( Schlegel et al, 2018 ).…”
Section: Modeling Codes: a Window Into Epithelial Functionmentioning
confidence: 99%
“…The molecular regulation of intestinal lipoprotein metabolism is still unclear, and van Loon et al [13] tested if the liver X receptor (LXR)-E3 ubiquitin ligase inducible degrader of LDLR (IDOL)-low-density lipoprotein receptor (LDLR) axis regulates intestinal expression of LDLR, and found that it is critical for maintaining cholesterol homeostasis in enterocytes. Vujić et al [14] demonstrated that suppressed intestinal expression of acyl-CoA:diacylglycerol acyltransferase 1 (DGAT1), the rate-limiting enzyme of triglyceride biosynthesis, reduces dietary cholesterol assimilation in the intestine, and consequently atherogenesis. This finding underlines the role of intestinal-derived lipoproteins in ASCVD.…”
Section: Atherogenic Lipoproteinsmentioning
confidence: 99%